Expression, purification and crystallization of the Crimean–Congo haemorrhagic fever virus nucleocapsid protein - Carter, S. D. (International Union of Crystallography, 2012)
Crimean–Congo haemorrhagic fever virus (CCHFV) is a member of the Nairovirus genus within the Bunyaviridae family of segmented negative-sense RNA viruses. This paper describes the expression, purification and crystallization of full-length CCHFV nucleocapsid (N) protein and the collection of a 2.1 Å resolution X-ray diffraction data set using synchrotron radiation. Crystals of the CCHFV N protein belonged to space group C2, with unit-cell parameters a = 150.38, b = 72.06, c = 101.23 Å, β = 110.70° and two molecules in the asymmetric unit. Circular-dichroism analysis provided insight into the secondary structure, whilst gel-filtration analysis revealed possible oligomeric states of the N protein. Structural determination is ongoing.